Coronavirus seasonality, respiratory infections and weather - Nichols, Gordon L.; Gillingham, E. L.; Macintyre, H. L.; Vardoulakis, S.; Hajat, S.; Sarran, C. E.; Amankwaah, D.; Phalkey, Revati (BMC infectious diseases, 2021)
The survival of coronaviruses are influenced by weather conditions and seasonal coronaviruses are more common in winter months. We examine the seasonality of respiratory infections in England and Wales and the associations between weather parameters and seasonal coronavirus cases.